Penerapan media dan buku ajar siswa berbasis meaningful learning pada materi bangun datar untuk meningkatkan berpikir kreatif siswa kelas III sekolah dasar - Normalasarie Normalasarie; Siti Aulia (Math Didactic: Jurnal Pendidikan Matematika, 2018)
Based on the results of observations and discussions with teachers at Pelambuan 7 Elementary School in Banjarmasin with class III teachers, it was concluded that students were still having difficulties in following mathematics learning, especially on flat-build material. The teaching materials that they use so far are ordinary textbooks and limited number of LKS and are not made by the teacher itself, so that they are not in accordance with the character of students. Meaningful learning is a process of connecting new information with relevant concepts contained in one's cognitive structure. The model used in this study is the Plomp model because it has a simple, systemic and clearly understood sequence, according to Plomp (Hobri 2010) there are five phases in designing this development, namely (1) Initial investigation phase (2) Design phase (3) Realization / construction (4) Evaluation and revision phase (5) Implementation phase. The results of this study produce student textbooks. Student textbooks consist of three parts, namely the introduction, discussion and closing. The results of expert and practitioner validation showed that the developed student textbooks were declared valid with an average score of 3.4. so that the student textbooks have met the practicality criteria. The effectiveness of student textbooks is determined from the analysis of (1) the mastery test of textbook material, (2) the activity of teachers and students, and (3) the results of interviews with students. Based on the trials that have been carried out, the results obtained are as much as 85% get a minimum score of 65, so that the classical completeness criteria have been met.